Nutritional Status, Lifestyle and Lipid Profile in Vegetarians - Pimentel,Carolina Vieira de Mello Barros (2019)
Abstract Background: Vegetarian diets have been linked to reduced risk of chronic noncommunicable diseases, since they positively modulate biochemical parameters, particularly those related with glycemic control and lipemia, and considered as potential strategy for weight control. Objective: To compare the nutritional status, lifestyle and lipid profile of adult vegetarians with omnivores in a sample of individuals in the city of São Paulo. Methods: This was a cross-sectional study. Anthropometric, biochemical and lifestyle variables were compared between vegetarians and omnivores. A significance level of 5% was considered for all analyses. Results: Vegetarians were more likely to practice physical activity (64.3% vs 42.5%, p = 0.056) and consuming dietary supplements (48.1% vs 20.5%, p = 0.012). There was no statistically significant difference for the variables: age, sex, triglycerides, total cholesterol and low-density lipoprotein between the two groups. Vegetarians had significantly lower weight [60.8 kg (56.7 - 69.4) vs 71.1 kg (58.0 - 75.4), p = 0.038], BMI [22.4 kg/m2 (20.9 - 23.8) vs 24.6 kg/m2 (21.7 - 26.1), p = 0.001], and waist circumference [(81.8 ± 8.2 vs 87.8 ± 10.9 cm, p = 0.003)], and higher high-density lipoprotein (54.88 ± 14.44 vs 47.30 ± 12.27 mg /dL p = 0.008) than omnivores. Conclusion: Compared with omnivores, vegetarians had a better nutritional status, with lower BMI and waist circumference, significantly higher levels of plasma lipoprotein high-density, and healthier lifestyle.